METAHEURISTICS UNTUK MENYELESAIKAN PERMASALAHAN VEHICLE ROUTING PROBLEM: PARTIAL COMPARISON OPTIMIZATION - Enty Nur Hayati; Antono Adhi; Lie Liana; Evitriani Evitriani; Retno Maulana Sari (Jurnal Ilmiah Dinamika Teknik, 2019)
Vehicle Routing Problem (VRP) is a problem of searching shortest route from origin point and back to the same point by considering transportation capacity. VRP is varian of Traveling Salesman Problem (TSP). In this research a metaheurstics method called Partial Comparison Optimization (PCO) was developed to search close optimal solution in order to solve combinatorial optimization such as TSP. Some data instance from TSPLIB was used to evaluate the performance of PCO. The numerical result showed that this proposed optimisation algorithm could achieve near optimum solution.